Efficacy of Suxiao Jiuxin Pill on Coronary Heart Disease: A Meta-Analysis of Randomized Controlled Trials - Ren, Li (Evid Based Complement Alternat Med, 2018)
Suxiao jiuxin pill is considered an effective ancillary drug in patients with coronary heart disease. Although numerous small, single-center clinical trials have been conducted, the benefits and harms of suxiao jiuxin pill remain controversial. We performed a meta-analysis to clarify the efficacy of suxiao jiuxin pill on patients with coronary heart disease. Randomized controlled trials were identified by using the Cochrane Library, PubMed, Web of Science, Embase, Wanfang, Weipu, and China Knowledge Resource Integrated databases (until June 2016). Pooled relative risks (RR), weighted mean differences (WMD), and 95% confidence intervals (95% CIs) were estimated using random-effects models. Forty-one trials involving 6276 patients were included in our analysis. Administration of suxiao jiuxin pill significantly improved electrocardiogram (ECG) results when compared with other therapies (RR 1.32, 95% CI 1.26 to 1.38, and P < 0.001). Subgroup analyses revealed that suxiao jiuxin pills improve ECG results more than salvia tablets (RR 1.54, 95% CI 1.41 to 1.67, and P < 0.001), isosorbide dinitrate (RR 1.14, 95% CI 1.21 to 1.44, and P = 0.001), nitroglycerin (RR 1.35, 95% CI 1.16 to 1.56, and P < 0.001), and other drugs (RR 1.32, 95% CI 1.21 to 1.44, and P < 0.001). Available evidence additionally suggests that suxiao jiuxin pills could significantly reduce total cholesterol (WMD −0.62 mmol/L, 95% CI −1.06 to –0.18 mmol/L, and P = 0.005) and low-density lipoprotein (LDL) levels (WMD −1.12 mmol/L, 95% CI −1.42 to −0.82 mmol/L, and P < 0.001) and increase high-density lipoprotein (HDL) levels (WMD 0.32 mmol/L, 95% CI 0.07 to 0.58 mmol/L, and P = 0.014). However, no significant differences were observed in total triglyceride levels, plasma viscosity, hematocrit, and fibrinogen. No incidences of adverse reactions were observed after administration of suxiao jiuxin pill. Improvements in ECG results and lipid profiles were also observed after suxiao jiuxin administration compared to other therapies. It also decreased low-cut and high-cut whole blood viscosity without significant adverse reactions.